Towards a common vision of climate security in Kenya: Workshop report - Medina, Leonardo; Belli, Anna; Caroli, Giulia; Dutta Gupta, Tanaya (CGIAR FOCUS Climate Security, 2022)
Climate change can potentially exacerbate the social, economic and political processes that lead to instability and conflict. Yet, there is insufficient localized and policy-relevant evidence on how exactly climate-related security risks may emerge across different geographic contexts. The ClimBeR initiative held a 3-day workshop to understand the climate action needs of Kenya and to explore the main challenges towards integrating the climate security nexus in Kenya's climate change policy frameworks and action strategies. This workshop brought together over 45 stakeholders from Kenya’s humanitarian, development, climate and peace sectors, including government representatives, NGOs, international organizations, and research institutes.